ANALISIS STRATEGI ISLAMIC COLLECTIVEENTREPRENEURSHIP (ICE): SOLUSI MENGATASI DESA TERTINGGAL - Dzaky Adam Thamrin; Boby Habibi; Dewi Permata Sari; Fauzul Hanif Noor Athief (Profetika: Jurnal Studi Islam, 2020)
The rural economic sector has a substansial role for the welfare of society and the economic support of nation. Data from Indonesian Ministry of Villages (2018) showed 13.232 underdeveloped villages in Indonesia due to economic reasons. The lack of human resources was the major reason. Therfore, the improvement of human resources throught entrepreneurship is needed. One of the successful village throught entrepreneurship is Gerdu Village in Karanganyar, which also has succeeded in becoming an islamic tourism village. The entrepreneurship strategy is carried out collectively based on islamic values or known as islamic Collective Entrepreneurship (ICE). Researchers try to find how far the effecticeness of ICE strategy as a solution for othe underdeveloped villages. This is a descriptive qualitative research with using observation for collecting data. The data is obtained through interviews with some informants: community leader, community representative, and district institution in Karanganyar. The result is the ICE strategy was carried out by Gerdu Village has three stages: 1. Education and Cooperation, 2. Implementation and Management, 3. Evaluation and Planning. In addition, the internal driving factor in ICE’s success lies in the activeness of village leader and youth in practicing islamic economics. The collaborationwith external parties such as BAZNAS, DISPARPORA, as well as other intitution around the village are actively helping in village development.